EVALUATION OF THE FUNCTIONAL STATE OF THE KIDNEYS IN HEALTHY AND PATIENTS WITH TYPE 1 DIABETES WITH DIFFERENT LEVELS OF ALBUMIN IN THE URINE - Kryvoviaz, Yu.O.; Vernigorodskiy, V.S.; Cherkasova L.А.; Drachuk, O.P.; Kordon, Yu.V. (World of Medicine and Biology, 2021)
The study analyzed the differences in the functional status of the kidneys in healthy and patients with type 1 diabetes with different levels of albumin in the urine. Significantly, higher values of microalbumin, creatinine, albumin-creatinine coefficient of urine and lower values of glomerular filtration rate according to Cockcroft-Gault, CKD EPI and cystatin C in sick men and women compared with the control group of persons of the same sex. The discrepancies and contradictions e of indicators comparison results in the subjects with different levels of albumin in the urine justified the need to use a full set of criteria for renal dysfunction in the division into comparison groups.